Parasitic fitness of a strain of Diachasmimorpha longicaudata (Hymenoptera, Braconidae) reared on irradiated larvae of a Vienna-8 strain of Ceratitis capitata (Diptera, Tephritidae) - Djellabi, B.; Herrero-Schell, Julieta; Ababsa, L.; Sekour, M.; Beitia, Francisco J. (ISHS, 2022)
Introduction: Ceratitis capitata (Wiedemann) (Diptera: Tephritidae) is a cosmopolitan pest that has invaded almost all temperate and tropical countries. Biological control of C. capitata is now well established in many American countries, but it is still limited in Europe. Recently, the use of the parasitoid Diachasmimorpha longicaudata (Ashmead) (Hymenoptera, Braconidae) by field releases in the Valencian Community (Eastern Spain) is being considered as a complement in the management of the pest by the Sterile Insect Technique (SIT). A semi-mass rearing of the parasitoid using irradiated larvae of a medfly Vienna-8 strain was started by the company Tragsa. The aim of this work is to assess the parasitic fitness of the parasitoid colony after several generations of semi-mass rearing. Materials and methods: The bioassay was performed analyzing different fitness-related parameters of the parasitoids: fecundity, percentage of parasitism and superparasitism, and the presence of ovipositors’ scars on medfly pupae. Two parasitoid colonies were compared: a laboratory colony (IVIA) reared on wild-type larvae (larvae from a rearing initiated and periodically refreshed with field individuals) for more than 50 generations and the semi-mass reared colony (Tragsa). Moreover, the two types of host larvae were analyzed as they could potentially affect adult parasitic fitness. Results and discussion: Results show that adults from the Tragsa colony have not lost parasitic fitness after 14 generations reared on irradiated Vienna-8 larvae. Medfly larvae show less suitability to be parasitized for both parasitoid colonies. Conclusion: We can conclude that the mass reared parasitoids are suitable to be released in the field for the biological control of the medfly.